MORPHOLOGICAL CHANGE OF VERB AND NOUN IN OLD, MIDDLE, AND MODERN ENGLISH - Rahmawan, Andi Dian (ELTICS Journal, 2014)
This library research aims to (1) identify effects of various colonialism on the change of morphological aspects of English Language and (2) explore the morphological change of verb and noun. Those two aims will give the readers a perspective of how language changes through the time. This is a library research which is conducted by collecting and processing data of various lexicons from a book entitled âA History of English Languageâ. The data processing is entirely based on some rules in a book entitled âSejarah Bahasa Inggrisâ written by Tarjana (1991). From the data processing, it is revealed that various colonizers âdemandâ a language change, especially morphological aspect, in order a language understanding between colonizers and the colony will grow. Besides,Â  morphological change will give us a clear description about natural characteristics that a language will always experience a change to accomodate the need of communicating effectively and efficiently. Â  Keywords: morphological change, English Language, colonialism